COVID-19 vaccines and a perspective on Africa. Issue 3 (March 2023) - Mantovani, Alberto; Rescigno, Maria; Forni, Guido; Tognon, Francesca; Putoto, Giovanni; Ictho, Jerry; Lochoro, Peter
Highlights: Over 30 vaccines against SARS-CoV-2 are in use worldwide, but the dissection of some of the immunological mechanisms is limited to only a few. Innate immunity activation by SARS-CoV-2 vaccines triggers adaptive immune responses, reactogenicity, and mechanisms of pathogen-agnostic protection (trained immunity). The lipid nanoparticles (LNPs) which carry mRNA vaccines activate a complex network of innate immune cells and cytokines, but the sensors involved remain to be fully defined. Trained innate immunity activated by LNPs, adenoviral vaccines, or unrelated vaccines such as live polio virus may be particularly relevant in African countries. The impact of genetics, microbiome, and prevalent infectious diseases, as well as the potency, breadth, and imprinting of immune responses in African countries, remains undefined. Mucosal vaccination eliciting strong IgA2 responses represents a holy grail because of its potential to inhibit infection and transmission. Vaccine inequality encompasses production and access to vaccination, as well as immunological resources, and this is relevant in African countries. Significance: An analysis of the landscape of the 30 SARS-CoV-2 vaccines in current use worldwide and their impact on innate and adaptive immunity are highly relevant; indeed, there are clear gaps in our knowledge and challenges related to low-income countries. We argue that examining vaccination responses in the African continent represents a clear opportunity to investigate fundamental questions, including the impact of genetics, microbial milieu, and prevalent diseases on SARS-CoV-2 vaccine-elicited immune responses. Abstract: Vaccines have dramatically changed the COVID-19 pandemic. Over 30 vaccines that were developed on four main platforms are currently being used globally, but a deep dissection of the immunological mechanisms by which they operate is limited to only a few of them. Here, we review the evidence describing specific aspects of the modes of action of COVID-19 vaccines; these include innate immunity, trained innate immunity, and mucosal responses. We also discuss the use of COVID-19 vaccines in the African continent which is ridden with inequality in its access to vaccines and vaccine-related immunological research. We argue that strengthening immunology research in Africa should inform on fundamental aspects of vaccination, including the relevance of genetics, trained innate immunity, and microbiome diversity.